SkSP-V Acceptance Sampling Plan based on Process Capability Index - Muhammad Aslam" (Science Faculty of Chiang Mai University, 2019)
In this paper, we present the SkSP-V acceptance sampling plan based on process capability index. The plan parameters of the proposed plan are determined by satisfying the producer’s risk and the consumer’s risk by minimizing the average sample number (ASN). The efficiency of the proposed plan is discussed over the existing acceptance sampling plan. Tables are discussed with the help of amplified pressure sensor data.